The history of stereology - Kolbaşı, Bircan; Güneş, Arzu; Keskin, İlknur (Nova Science Publishers, Inc., 2024)
Stereology is a methodological discipline employed to describe a 3-dimensional structure using 2-dimensional images with the aid of mathematics, geometry, and statistical sciences. It provides methods for measuring the surfaces and volumes of solids such as prisms, cubes, spheres, and polyhedral shape structures and total number of particles in a region or organ. This methodological science is a multidisciplinary one, since its methods are used in medicine and biology, mineralogy, materials science, agriculture, and forestry. The concept of stereology was first introduced in 1777 by the French naturalist George Buffon in his paper "Buffon's needle problem." Soon after the establishment of the International Society for Stereology (ISS) in 1961, the concept of stereology began having a major impact on sciences such as materials science, petrography, and microscopy. In the 60 years since interdisciplinary scientists first recognized it as a modern science, stereology has made rapid advances in parallel with the development of computer-based methods. Topology, mathematics, statistics, and statistical geometry have also contributed greatly to the development of stereology. The rapid historical development of stereology encourages us to believe that it will make an even greater contribution to many sciences in the future by extending and improving its methods. This review discusses the history of stereology and the developments made in that field to date.
Keywords: Disector; Microscopy; Quantitation; Stereology; Three-Dimensional